Blockchain Technology as Authenticated System for Smart Universities - Choi, Lee Kyung; Sunarya, Po Abas; Fakhrezzy, Muhammad (Pandawan Sejahtera Indonesia, 2022)
Many industries and universities are interested in blockchain technology, which is a growing field of interest. The Digital Data Storage System (DDS) consists of many servers (multi-server). Blockchain technology allows data to be copied and authenticated across servers. Many people believe that blockchain is only used for cryptocurrencies, but that's not entirely correct. Bitcoin, one of the most well-known cryptocurrencies, heavily relies on the technology. However, in reality, the use of blockchain is not limited to cryptocurrencies. One way that blockchain technology can be used is for data processing in universities. In this study, the author looks at how it can be used to improve student records, document transactions, and more.The research method used in this study is the